Investigating Earth's Formation History Through Copper and Sulfur Metal‐Silicate Partitioning During Core‐Mantle Differentiation. Issue 10 (8th October 2018) - Mahan, B.; Siebert, J.; Blanchard, I.; Badro, J.; Kubik, E.; Sossi, P.; Moynier, F.
Abstract: Identifying extant materials that act as compositional proxies for Earth is key to understanding its accretion. Copper and sulfur are both moderately volatile elements; however, they display different geochemical behavior (e.g., phase affinities). Thus, individually and together, these elements provide constraints on the source material and conditions of Earth's accretion, as well as on the timing and evolution of volatile delivery to Earth. Here we present laser‐heated diamond anvil cell experiments at pressures up to 81 GPa and temperatures up to 4, 100 K aimed at characterizing Cu metal‐silicate partitioning at conditions relevant to core‐mantle differentiation in Earth. Partitioning results have been combined with literature results for S in Earth formation modeling to constrain accretion scenarios that can arrive at present‐day mantle Cu and S contents. These modeling results indicate that the distribution of Cu and S in Earth may be the result of accretion largely from material(s) with Cu contents at or above chondritic values and S contents that are strongly depleted, such as that in bulk CH chondrites, and that the majority of Earth's mass (~3/4) accreted incrementally via pebble and/or planetesimal accretion. Plain Language Summary: Experiments wherein molten metal and silicate (rock‐building) phases unmix themselves due to their physical properties, that is, metal‐silicate partitioning, can be conducted at the high temperatures and pressures (HP‐HT) that characterized Earth's differentiation into a core and mantle. The redistribution of elements between the metal and silicate phases—their partitioning—during this process can be measured and mathematically described, then placed into numerical models to better understand Earth's formation history. Here we have mathematically characterized the HP‐HT partitioning of copper, combined this with results for sulfur from literature, and input these characterizations into numerical models that track their distribution between Earth's core and mantle as it grows to its present mass. Copper and sulfur were chosen because they display different sensitivities to the physical mechanisms that govern planetary formation, and we can leverage this to better understand Earth's formation and differentiation history. Our results indicate that ~75% of Earth's precursor materials grew incrementally from relatively small bits of material—on average ~0.1% of Earth's mass or less—that is most compositionally similar to meteorite classes that are made up of iron‐rich metal and silicate solids (chondrules) that are depleted in easily vaporized (volatile) elements, especially sulfur. Key Points: Modeling Earth's formation from chondritic material generates bulk silicate Earth Cu contents; however, this generates an overabundance of S Co‐accretion of metal and silicate chondrules, akin to those in CH chondrites, can generate bulk silicate Earth abundances for Cu and S Cu results indicate that most chondritic materials require ~75% of Earth's accretion via incremental growth to reach minimum BSE Cu contents